IMPORTANCE OF INTERGENERATIONAL RELATIONS IN THE CONTEXT OF GLOBAL POPULATION AGEING – POLISH EXAMPLES - Jolanta Mackowicz (European Scientific Journal, ESJ, 2014)
This article deals with the issue of building intergenerational relations in the context of progressive population ageing. The author raises three issues while discussing this topic. Firstly, she considers the importance of a positive image of the elderly and overcoming age-related stereotypes. Secondly, she refers to some contemporary threats that endanger intergenerational relations or severely hamper their development. Finally, the author identifies necessary actions to be taken in various areas of social life that could facilitate building and maintaining positive relations between generations.